IMPLEMENTASI DAN ANALISIS KURIKULUM BAHASA ARAB BERBASIS 4C DI MTS NURUL HIJRAH KANDIS - Ahmad Jezy; M. Apip; Wahyuni Saeran Abdullah (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the implementation of the 4C-based curriculum (Critical Thinking, Communication, Collaboration, Creativity) in Arabic language learning at MTs Nurul Hijrah Kandis. Using a descriptive qualitative approach, data were collected through classroom observations, interviews, and document analysis to obtain an in-depth understanding of teachers’ strategies, learning activities, and challenges in applying the 4C framework. The findings reveal that the integration of 4C is reflected in various instructional practices, including role-playing for speaking skills (kalam), the use of unvowelled Arabic texts to foster critical thinking in reading skills (qira’ah), group discussions to promote collaboration, and creative writing and bulletin board projects to enhance creativity. The implementation of 4C has improved student participation, confidence, and functional language skills. However, several obstacles were identified, such as limited instructional time, students’ low foundational Arabic skills, and the lack of innovative learning media. This study concludes that the application of the 4C curriculum at MTs Nurul Hijrah Kandis has been relatively effective but still requires greater support in terms of facilities, teacher training, and learning culture development to achieve optimal outcomes.